ARTIFICIAL INTELLIGENCE AS A FACTOR IN THE TRANSFORMATION OF THE MODERN RUSSIAN LANGUAGE: LEXICAL, SYNTACTIC, AND PRAGMATIC ASPECTS - Murodova Dilnurakhon Sarvarjon qizi (International Journal of Literature and Language Studies, 2026)
This article presents a comprehensive analysis of the impact of artificial intelligence (AI) technologies, particularly large language models and neural machine translation systems, on the development of the modern Russian language. Based on a corpus analysis of internet discourse, data from explanatory dictionaries of neologisms, and experimental observations of students’ speech behavior, the author identifies the main directions of linguistic change. These include the emergence of more than fifty new lexical units (such as prompt, neural network, tokenization, AI hallucination, etc.); syntactic convergence manifested in the increasing use of elliptical constructions and infinitive phrases characteristic of user prompts; and stylistic homogenization of written discourse under the influence of chatbot-generated template responses. The study also examines the risks associated with declining orthographic literacy and critical thinking resulting from excessive reliance on AI assistants. In conclusion, the article proposes a model of “digital linguistic competence” as an essential component of education in the era of generative artificial intelligence. The article is intended for linguists, Russian language educators, specialists in digital communication, and experts in AI ethics.